2020
DOI: 10.1371/journal.pone.0236774
|View full text |Cite
|
Sign up to set email alerts
|

The ITS region provides a reliable DNA barcode for identifying reishi/lingzhi (Ganoderma) from herbal supplements

Abstract: The dietary supplement industry is rapidly growing yet, a recent study revealed that up to 60% of supplements may have substituted ingredients, some of which can be harmful contaminants or additives. When ingredients cannot be verified morphologically or biochemically, DNA barcoding complemented with a molecular phylogenetic analysis can be a powerful method for species authentication. We employed a molecular phylogenetic analysis for species authentication of the commonly used fungal supplement, reishi (Ganod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
(152 reference statements)
0
9
0
Order By: Relevance
“…Many researchers have reported that ITS region has the advantages of high intra-specific conservation, large inter-specific variation, small fragment, easy amplification, easy analysis and high success rate for species identification [ 20 , 21 ]. Similar results were found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have reported that ITS region has the advantages of high intra-specific conservation, large inter-specific variation, small fragment, easy amplification, easy analysis and high success rate for species identification [ 20 , 21 ]. Similar results were found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study had shown that ITS2 has ability to discriminate approximately 13307 genus and 5240 species accessed from GenBank and no argument on considering ITS2 as universal barcode for wide taxa range of medicinal plant [13]. In addition, Pang et al, reported that ITS2 was able to distinguish 100% correctly species from adulterants, however, it was not easy to discriminate herbal products, because of degraded DNA and substituted by other species [11,20]. Therefore, high quality of DNA extracted was a crucial step in any DNA molecular techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Ganoderma spp. is now marketed as a dietary supplement in the Unites States of America and the European Union [18] . Polysaccharides, triterpenoids, alkaloids, and proteins extracted from Ganoderma spp.…”
Section: Introductionmentioning
confidence: 99%